(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
This paper assesses the effects of world cotton prices on poverty among India’s cotton-producing households. This paper provides a discussion of the poverty line for India as well as estimates of the national levels of rural and urban poverty and the decline of those levels from 1973–1974 to 2004–2005.